Individual and public health consequences associated with a missed diagnosis of pulmonary tuberculosis in the emergency department: A retrospective cohort study. - Courtney Heffernan; Catherine Paulsen; Leyla Asadi; Mary-Lou Egedahl; Brian H Rowe; James Barrie; Richard Long (PLoS ONE)
Objectives To determine: i) the emergency department (ED) utilization history of pulmonary tuberculosis (PTB) patients, and ii) the potential individual and public health consequences of a missed diagnosis of PTB in this setting. Design Retrospective observational cohort study. Participants Patients with PTB aged >16 years diagnosed between April 1, 2010 and December 31, 2016 in the Province of Alberta, Canada. Methods We identified valid new cases of PTB from a provincial registry and linked them to ED attendees in administrative databases. Visits are considered 'PTB', pulmonary 'other', and non-pulmonary based on the most responsible discharge diagnosis. Individual consequences of a missed diagnosis included health system delay and PTB-related death; public health consequences included nosocomial ED exposure time and secondary cases. Results Of 711 PTB patients, 378 (53%) made 845 ED visits in the six months immediately preceding the date of diagnosis. The most responsible ED discharge diagnosis was PTB in 92 (10.9%), pulmonary 'other' in 273 (32%) and non-pulmonary in 480 (56.8%). ED attendees had a median (IQR) health system delay of 27 (7,180) days and, compared to non-ED attendees were more likely to die a TB-related death 5.9% vs 1.2%, p = 0.001. Emergency attendees generated 3812 hours of ED nosocomial exposure time, and 31 secondary cases (60.8% of all secondary cases reported). Mycobacterium tuberculosis isolates from ED-attendees were more likely than non-attendees to be clustered-i.e., have an identical DNA fingerprint with another isolate (27% vs. 21%, p = 0.037). Conclusions ED utilization by PTB patients, and related consequences, are substantial. EDs are a potential resource for earlier PTB diagnosis.